ESTUTI: Ethnomedicine and Transformation of Ice Cream to Prevent Stunting Using Family Medicinal Plants in Tanggamus - Diah Kartika Putri; Fina Aulika Lestari; Taufiki Miftausakina; Amalia Siti Nurazizah; Adi Saputra; Vicko Suswidiantoro; Wina Safutri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
The stunting prevalence rate for Lampung Province based on the 2022 SSGI averages 15.2% and Tanggamus Regency is ranked fourth with the highest stunting prevalence, namely 20.4%. This research aims to use TOGA as a spearhead for treating stunting in toddlers using Moringa leaves and ginger rhizomes. Moringa leaves (Moringa Oleifera Lam.) can be used as a potential alternative source of protein and calcium to meet children's nutritional needs. The ESTUTI formulation is divided into 3 formulations with differences in Moringa leaf extract and ginger, namely 25gr/100ml water, 50gr/100ml water, and 75gr/100ml water. Tests in this research include organoleptic tests, hedonic tests and melting point tests. The results show that the most preferred "ESTUTI" formulation is F1 with the formula Moringa leaves: ginger 25gr/100ml water. The combination of ginger and Moringa leaves is rich in nutritional value as an anti-stunting agent which the community responded well to during outreach. So it is hoped that it will be able to provide information on snacks as functional foods that have new qualities and qualities as anti-stunting by utilizing plants that grow abundantly around and developing the community's innovation and entrepreneurship experience.Key words: Curcuma xanthorriza; Ethnomedicine; Formulation; Ice cream; Moringa oleifera Lam; Stunting